Histoplasmosis in immunocompetent individuals living in an endemic area in the Brazilian Southeast - Faiolla,Rivian Christina Lopes (2013)
Introduction The distribution of infection by Histoplasma capsulatum in Brazil is heterogeneous, and the number of cases affecting immunocompetent individuals is relatively small. This study reports the epidemiological and clinical data regarding histoplasmosis in non-immunosuppressed individuals. Methods The study included only the immunocompetent patients with histoplasmosis who were diagnosed between 1970 and 2012 at a university hospital located in Ribeirão Preto, State of São Paulo, Brazil. Clinical and epidemiological data were collected retrospectively from the patient records. Results Of the 123 patients analyzed, 95 had an active disease that manifested in the different clinical forms of histoplasmosis. Men were the predominant gender, and most patients resided in the Northeast of the State of São Paulo and in the nearby municipalities of the State of Minas Gerais. The risk factors for acquiring histoplasmosis and prolonged contact in a rural environment were recorded in 43.9% and 82.9% of cases, respectively. Smoking, alcoholism, and comorbidity rates were high among the patients with the chronic pulmonary and subacute/chronic disseminated forms of histoplasmosis. Many patients achieved clinical cure spontaneously, but 58.9% required antifungals; the disease lethality rate was 5.3%. Conclusions Immunocompetent individuals manifested the diverse clinical forms of histoplasmosis over a period of 4 decades, revealing an additional endemic area of this fungal disease in the Brazilian Southeast.